2017
DOI: 10.1089/aid.2016.0017
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analyses Reveal Gene Influence on HIV Disease Progression and HIV-1C Acquisition in Southern Africa

Abstract: Sub-Saharan Africans infected with HIV-1C make up the largest AIDS patient population in the world and exhibit large heterogeneity in disease progression before initiating antiretroviral therapy. To identify host variants associated with HIV disease progression, we performed genome-wide association studies on a total of 556 treatment-naive HIV-infected individuals in Botswana. We characterized the pattern of HIV disease progression using a novel functional principal component analysis, which can better capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…A validation test was done in data from three independent American cohorts, and no significant association was observed around the two genes ( HCG22 and CCNG1 ). SNPs that were found to associate with HIV infection and progression in previous studies did not appear in the top 100,000 p-values in this study (Xie et al, 2017).…”
Section: A Global Perspective Of Gwas Of Hiv-1mentioning
confidence: 47%
See 3 more Smart Citations
“…A validation test was done in data from three independent American cohorts, and no significant association was observed around the two genes ( HCG22 and CCNG1 ). SNPs that were found to associate with HIV infection and progression in previous studies did not appear in the top 100,000 p-values in this study (Xie et al, 2017).…”
Section: A Global Perspective Of Gwas Of Hiv-1mentioning
confidence: 47%
“…GWAS of HIV-1 have also been performed in other populations, African Americans, Hispanics, Chinese, and Africans (Pelak et al, 2010; Pereyra et al, 2010; Petrovski et al, 2011; Wei et al, 2015; Xie et al, 2017). Pereyra et al identified an intergenic SNP rs2523590 in Hispanics, Europeans, and Americans.…”
Section: A Global Perspective Of Gwas Of Hiv-1mentioning
confidence: 99%
See 2 more Smart Citations
“…Host genetic diversity has an important role in either disease susceptibility or resistance [ 4 , 5 ]. However, the positive role of different genes in HIV/AIDS progression has still remained controversial [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%